Influence Of Price And Product Quality On Consumer Satisfaction In Royyan Gems Shop In Martapura City, Banjar Regency South Borneo - Abdul Kadir; Fredy Jayen; Asruni (Archives of Business Research, 2022)
The purpose of this study was to examine and analyze the effect of price and product quality on consumer satisfaction at the Royyan Permata Store in Martapura City, Banjar Regency, South Kalimantan. The sample in this study were 30 consumers. The sampling technique used in this research is purposive sampling method. Data analysis in this study used Multiple Linear Regression Analysis, while hypothesis testing used F, R2, and t-test. The results showed that product quality had a positive and significant effect on consumer satisfaction and was acceptable. These results also prove the first hypothesis, that product quality has an effect on consumer satisfaction at the Royyan Permata Store, Martapura City. The results show that t arithmetic is greater than t table (2.563 > 1.989), with a significant value of 0.012 which is smaller than 0.05 (0.012 < 0.05), and the regression coefficient has a positive value of 0.255. Price has a positive and significant effect on consumer satisfaction and can be accepted. These results also prove the second hypothesis, that price has an effect on consumer satisfaction at the Royyan Permata Store in Martapura City. The results show that t arithmetic is greater than t table (4,470 1,989), with a significant value of 0.000 less than 0.05 (0.000 < 0.05), and the regression coefficient has a positive value of 0.389.